RELEVANSI PENGAJARAN NILAI-NILAI PERJANJIAN LAMA DALAM PENDIDIKAN AGAMA KRISTEN DI ERA MODERN - Heni Yopy Tati; Harun Y Natonis (CV. ADIBA AISHA AMIRA, 2025)
Christian Religious Education (PAK) is the main foundation in the formation of character, morals, and spirituality of Christians. The values ​​contained in the Old Testament (OT) are not only a historical legacy, but are also relevant to answer the challenges of education in the modern era. This study aims to analyze the relevance of teaching Old Testament values ​​in contemporary Christian Religious Education. By using the literature study method, this study found that values ​​such as obedience, justice, love, and social responsibility taught in the OT remain relevant to shape the character of Christian students. The implementation of these values, if contextualized creatively, can be a solution to the moral and spiritual crisis in the era of globalization.